Сучасна історична енциклопедистика: здобутки і перспективи розвитку - Смолій, В.А.; Боряк, Г.В. (Вісник НАН України, 2015)
Висвітлено концептуальні засади, передумови і подальший розвиток унікального академічного проекту — галузевого універсального довідника «Енциклопедія історії України». Розглянуто еволюцію й трансформацію енциклопедичних практик на рубежі ХХІ ст. Проаналізовано процес переходу до формату електронного мультимедійного енциклопедичного ресурсу і
перспективи мережевих енциклопедичних проектів в Україні. Освещены концептуальные основы, предпосылки и дальнейшее развитие уникального академического проекта —
отраслевого универсального справочника «Энциклопедия истории Украины». Рассмотрена эволюция и трансформация энциклопедических практик на рубеже XXI века. Проанализирован процесс перехода в формат
электронного мультимедийного энциклопедического ресурса и перспективы сетевых энциклопедических проектов в Украине. The implementation of the unique academic project — a new sectoral universal reference book ‘The Encyclopedia of History
of Ukraine’ is on time. The article highlights its conceptual principles, conditions and circumstances. The evolution
and transformation of encyclopedic practices from the end of 1990s to the beginning of 2000s are examined. The perspectives
of the project’s development are analyzed. In particular, preparation of the volume Ukraine — Ukrainians, additional
volumes, and transition to the format of electronic multimedia encyclopedic source are reviewed. The meaning of
the latter in Ukrainian and global encyclopedistics is characterized. The features of the network encyclopedic projects in
Ukraine are researched.